Self‐Consistent Field Theory of Inhomogeneous Polymeric Systems: A Variational Derivation. Issue 4 (28th January 2019) - Shi, An‐Chang
Abstract: The self‐consistent field theory (SCFT) is a powerful framework for the study of the phase behavior and structural properties of many‐body systems. In particular, polymeric SCFT has been successfully applied to inhomogeneous polymeric systems such as polymer blends and block copolymer melts. The polymeric SCFT is commonly derived using field‐theoretical techniques. Here, an alternative derivation of the SCFT equations and SCFT free energy functional using a variational principle is provided. Numerical methods of solving the SCFT equations and applications of the SCFT are also briefly introduced. Abstract : The Gibbs‐Bogoliubov‐Feynman variational principle provides a theoretical framework to derive the mean‐field theory, which could be cast in the form of a self‐consistent field theory, for any statistical mechanical systems via a single‐particle decomposition of the total probability distribution. In particular, this generic approach provides an alternative derivation of the self‐consistent field theory for inhomogeneous polymeric systems.